Analisis Peluang dan Tantangan Pemanfaatan Metaverse Sebagai Pemasaran Digital - Wahyu Firmansyah; Dwi Desi Yanti; Nabilla Amelia Pratiwi; Tata Sutabri (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Metaverse is a three-dimensional virtual world connected via the internet, which allows users to interact with realistic digital environments. This concept has attracted the attention of many parties, including in the context of digital marketing. Utilizing metaverse technology in digital marketing has several opportunities and challenges. These opportunities include helping users interact with realistic digital environments, changing the way people sell and advertise, and improving social media platforms by providing greater freedom. However, the use of metaverse technology also has challenges, such as digital data security, a lack of humanity in digital interactions, and difficulties in applying digital literacy. This article aims to analyze the opportunities and challenges of using the metaverse as digital marketing. By understanding and overcoming these challenges, companies can utilize the potential of the metaverse as a digital marketing medium more effectively and responsibly.